ROS-scavenging tetrahedral framework nucleic acids: reprogramming the pathological microenvironment for oral tissue regeneration - Jiahui Xiong; Wuxiao Cui; Xiao Fu; Zhen Zhao; Yiliu Zhou; Bo Huang; Mei Zhang; Yunfeng Lin (Oral Science and Homeostatic Medicine, 2026)
Abstract The structural deterioration observed in maxillofacial skeletal conditions and associated mucosal tissues is fundamentally governed by a vicious cycle of sustained immunological activation and severe oxidative stress. Consequently, this continuous reactive oxygen species (ROS) accumulation directly fuels the etiology of debilitating diseases, notably bisphosphonate-related osteonecrosis of the jaw (BRONJ), oral submucous fibrosis (OSF), and periodontitis. Conventional therapeutic regimens often exhibit compromised localized efficacy or induce severe systemic adverse effects. To surmount these delivery impediments, tetrahedral framework nucleic acids (tFNAs) have emerged as versatile three-dimensional DNA nanostructure platforms. Characterized by high structural rigidity, intrinsic radical-scavenging bioactivity, rapid cellular internalization, and precise programmability, tFNAs enable the targeted co-delivery of regulatory oligonucleotides, small-molecule antioxidants, and bioactive peptides. This review evaluates how ROS modulate downstream oxidative stress and inflammatory networks to drive tissue destruction and bone metabolic imbalances. Furthermore, we examine structural optimization strategies, including the integration of tFNAs into hydrogel matrices, the incorporation of pH-responsive lysosomal escape elements, and the conjugation of targeting surface ligands. Preclinical evidence demonstrates that functionalized tFNAs networks effectively disrupt the self-amplifying oxidative stress-inflammation cascade, remodeling hostile microenvironments to promote structural tissue regeneration. To conclude, this review delineates major clinical translation hurdles, including industrial scale-up and pharmacokinetic elimination profiles. These considerations establish a conceptual baseline for engineering future targeted oxidative therapies.